2008
DOI: 10.1080/01635580701624712
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Berries and Ellagic Acid Diminish Estrogen-Mediated Mammary Tumorigenesis ∈ ACI rats

Abstract: Estrogen acts as a complete mammary carcinogen in ACI rats. Prevention studies in this model allowed us to identify agents that are effective against estrogen-induced mammary carcinogenesis. In this study, we investigated efficacy of dietary berries and ellagic acid to reduce estrogen-mediated mammary tumorigenesis. Female ACI rats (8-9 wk) were fed either AIN-93M diet (n = 25) or diet supplemented with either powdered blueberry (n = 19) and black raspberry (n = 19) at 2.5% wt/wt each or ellagic acid (n = 22) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 46 publications
7
101
1
Order By: Relevance
“…This study also demonstrated that the anthocyanin fraction of black raspberries (BRB) was as effective in preventing chemically-induced esophageal tumors in rats as whole BRB powder [6]. Our own studies have shown significant inhibition of breast cancer in the rat model by both blueberry (BB) and BRB, indicating that berries are chemopreventive beyond the GI tract [7][8][9]. Our studies with BB diet have also shown that berry anthocyanidins are bioavailable beyond the GI as we could detect all anthocyanidins in lung tissues [10].…”
Section: Introductionmentioning
confidence: 77%
“…This study also demonstrated that the anthocyanin fraction of black raspberries (BRB) was as effective in preventing chemically-induced esophageal tumors in rats as whole BRB powder [6]. Our own studies have shown significant inhibition of breast cancer in the rat model by both blueberry (BB) and BRB, indicating that berries are chemopreventive beyond the GI tract [7][8][9]. Our studies with BB diet have also shown that berry anthocyanidins are bioavailable beyond the GI as we could detect all anthocyanidins in lung tissues [10].…”
Section: Introductionmentioning
confidence: 77%
“…Ellagic acid. Ellagic acid, a component in berries (blueberry, strawberry, and red raspberry), was reported to reduce oxidative DNA damage both in vitro and in vivo (4,5). In vitro, ellagic acid has demonstrated a >95% inhibition of 8-oxodeoxyguosine (8-oxodG) production.…”
Section: A Dietary Antioxidantsmentioning
confidence: 99%
“…[22][23][24][25][26][27][28][29] These data demonstrated that pomegranate phytochemicals provide protection against various cancer-related processes.…”
mentioning
confidence: 82%